The Effect of the Missouri Mathematics Project Learning Model on Students' Mathematical Communication Ability - Indriani, Rina; Angraini, Lilis Marina (EDUPEDIA Publisher, 2025)
Mathematical communication is one of the most important mathematical abilities that students must learn. Students' ability to communicate mathematical concepts orally or in writing is known as mathematical communication ability. Therefore, this research aims to determine how the Missouri Mathematics Project (MMP) model affects students' mathematical communication ability. With the Nonequivalent Control Group Design, The quantitative research method and type used in this research is experimental. Purposive sampling is a technique used for sampling which is an experimental class of the control class The research instrument used was a test. The data analysis in this study used parametric tests. The results of this research show that the class. is an experimental class that has a higher value when juxtaposed with the class analysed with descriptive analysis. The results of the hypothesis were obtained based on the t-test that it was significant. Thus, it is rejected and accepted, it is proven that the influence of the Missouri Mathematics Project (MMP) model on students' mathematical communication ability is obtained.